Early recognition of ipilimumab‐related autoimmune hypophysitis in patients with metastatic melanoma: Case studies and recommendations for management. Issue 2 (9th April 2015) - Tiu, Crescens; Pezaro, Carmel; Davis, Ian D; Grossmann, Mathis; Parente, Phillip
Abstract Ipilimumab is a human anti‐CTLA‐4 monoclonal antibody recently approved for the treatment of advanced melanoma. Stimulation of T‐cell activity unmasks antitumor activity, but can cause immune‐related adverse events. Autoimmune hypophysitis is of particular importance because its presentation can be subtle but life threatening. We present two cases where early recognition of ipilimumab‐related autoimmune hypophysitis led to timely intervention and low subsequent morbidity, without compromise of antitumor effects. We provide recommendations for detection and management of this potentially life‐threatening complication of ipilimumab.